Polystyrene Supported Coordination Compounds of Dibasic Tridentate Schiff Base Derived from Glycine - Kumar, D.; Singh, A.K.; Syamal, A. (Asian Journal of Chemistry, 2016)
The reaction of appropriate metal ions and the polystyrene-supported dibasic tridentate Schiff base (PS-LH2) derived from the condensation of chloromethylated polystyrene, 3-formylsalicylic acid and glycine in DMF produces polystyrene supported coordination compounds of the types: PS-LM·DMF (where M = Cu, Zn, Cd, MoO2, UO2); PS-LFeCl·2DMF; PS-LZr(OH)2-2DMF and PSLM'·3DMF (where M' = Co, Mn, Ni). These compounds have been characterized by elemental analyses, IR, reflectance, ESR spectral and magnetic susceptibility measurements. PS-LCu·DMF is square planar, PS-LM·DMF(M = Zn, Cd) is tetrahedral; PS-LMO2·DMF(M = Mo, U); PS-LFeCl-2DMF and PS-LM'·3DMF (M' = Co, Mn, Ni) are octahedral; while PS-LZr(OH)2-2DMF is pentagonal bipyramidal. The coordination compounds of Cu(II), Fe(III), Co(II), Mn(II) and Ni(II) are paramagnetic, while others are diamagnetic.